Optimization Study of Air-Based Cooling Photovoltaic Roofs: Experimental and Numerical Analysis - Yi He; Yibing Xue; Yingge Zhang (Energies)
The rapid growth of photovoltaic (PV) installed capacity has driven advancements in photovoltaic technology, such as integrating PV panels into building envelopes. Temperature increases are known to negatively impact PV panel performance. This study investigates and optimizes the design of air-based cooling systems for PV roofs using experimental and numerical analyses, leveraging free natural convection for cooling. Experimental measurements included air inlet/outlet, PV panel, and roof surface temperatures. The primary parameters examined in Computational Fluid Dynamics (CFD) for the numerical study were the heights and widths of the air channels between the panels and the rooftop, with heights ranging from 25 mm to 75 mm and widths varying from 200 mm to 400 mm. There are good agreements between the numerical results and experimental measurements after model validation. The results reveal significant temperature non-uniformity across the surface of the PV panels, with a maximum temperature difference of 16.50 °C. The shading effect of the PV panels resulted in an average reduction in roof surface temperature by 12.90 °C. Parametric studies showed that changes in height had a more pronounced effect on cooling than in width. The optimal design was identified with a channel size of 75 mm × 400 mm, resulting in the lowest average PV panel temperature of 65.21 °C and enhanced temperature uniformity, with maximum efficiency reaching 11.54%.